Threshold Dynamics of a Diffusive Herpes Model Incorporating Fixed Relapse Period in a Spatial Heterogeneous Environment. (30th December 2021) - Lu, Yueming; Yang, Wei; Ji, Desheng
Abstract : In this paper, we aim to establish the threshold-type dynamics of a diffusive herpes model that assumes a fixed relapse period and nonlinear recovery rate. It turns out that when considering diseases with a fixed relapse period, the diffusion of recovered individuals will lead to nonlocal recovery term. We characterize the basic reproduction number, ℜ 0, for the model through the next generation operator approach. Moreover, in a homogeneous case, we calculate the ℜ 0 explicitly. By utilizing the principal eigenvalue of the associated eigenvalue problem or equivalently by ℜ 0, we establish the threshold-type dynamics of the model in the sense that the herpes is either extinct or close to the epidemic value. Numerical simulations are performed to verify the theoretical results and the effects of the spatial heterogeneity on disease transmission.